Implementation of child rights in the children's homes in Malaysia - Nalasami, P.R.; Bakar, S.H.A.; Yusoff, J.Z.; Wahab, H.A.; Omar, N.; Islam, M.R. (John Wiley & Sons, 2015)
The objective of this study was to examine the implementation of the Convention on the Rights of the Child (CRC) in the Children Homes under the Social Welfare Department (SWD) in Malaysia. Data was collected from 402 registered children who were staying in six Children Homes across the country. This study employed self-report surveys where multiple data collection methods, such as face-to-face structured interviews, key informant interviews (KIIs), and documentation survey, were used. The study found that the SWD failed to comply with most of the commitments of CRC in Children Homes at its implementation level, and it is still needs based. The findings of this study present important guidelines for government and policy makers in improving child welfare services in the Children Homes in Malaysia.